Exploring the Influence of Learning Motivation and Socioeconomic Status on College Students’ Learning Outcomes Using Self-Determination Theory - Li, Hao; Peng, Michael Yao-Ping; Yang, Mingyue; Chen, Chun-Chun (Frontiers in Psychology, 2020)
Higher education, with the function of cultivating human capital, has already become the key focus of developed countries in the world. From Ministry of Education to higher education institutions, all of them are dedicated to enhancing student learning outcomes. Among them, social and educational problems derived from disadvantaged groups have long been hindering the development of individuals and the whole country. This study attempts to examine the learning motivation types of economically disadvantaged and non-disadvantaged college students, and evaluate the relationship between learning modes and learning outcomes from a self-determination theory perspective. In this study, 817 valid questionnaires were collected to compare the two sample groups in terms of learning path. The study shows that the non-economically disadvantaged students are superior to disadvantaged ones in terms of role identity, academic identity, explorative learning, exploitative learning, cognitive and non-cognitive gains. In regard to path analysis, economically disadvantaged students are significantly superior to non-disadvantaged students in the face of positive influence of academic identity on different learning modes and positive influence of explorative learning on cognitive and non-cognitive gains. Finally, this study proposes some suggestions specific to theoretical mode and future study based on the conclusions.